Systematic Environmental Impact Assessment for Non-natural Reserve Areas: A Case Study of the Chaishitan Water Conservancy Project on Land Use and Plant Diversity in Yunnan, China - Zhu, Zhi-Xin; Zhao, Kun-Kun; Lin, Qin-Wen; Qureshi, Salman; Ross Friedman, Cynthia; Cai, Guo-Yin; Wang, Hua-Feng (Frontiers in Ecology and Evolution, 2017)
Environmental impact assessment before and after the establishment of a Water Conservancy Project (WCP) is of great theoretical and practical importance for assessing the effectiveness of ecological restoration efforts. WCPs rehabilitate flood-damaged areas or other regions hit by disasters by controlling and redistributing surface water and groundwater. Using Geographic Information System (GIS) and Composite Evaluation Index (CEI) in predictive modeling, we studied the degree to which a WCP could change land use, plant communities, and species diversity in Yunnan, China. Via modeling, we quantified likely landscape pattern changes and linked them to naturality (i.e., the percentage of secondary vegetation types), diversity, and stability together with the human interferences (e.g., conservation or restoration project) of an ecosystem. The value of each index was determined by the evaluation system, and the weight percentage was decided through Analytical Hierarchy Process (AHP). We found that minor land-use changes would occur after the Chaishitan WCP was theoretically established. The greatest decline was farmland (0.079 %), followed by forest (0.066 %), with the least decline in water bodies (0.020 %). We found 1076 vascular plant species (including subspecies, varieties and form) belonging to 165 families and 647 genera in Chaishitan irrigation area before the water conservancy establishment. The naturality and diversity decreased 11.18 % and 10.16 % respectively. The Composite Evaluation Index was 0.92, which indicated that Chaishitan WCP will enhance local landscape heterogeneity, and it will not deteriorate local ecological quality. Our study proposes a comprehensive ecological evaluation system for this WCP and further suggests the importance of including the ecological and environmental consequences of the WCP, along with the well-established socioeconomic evaluation systems for non-natural reserve areas. We conclude that the Chaishitan WCP will have minor environmental impacts on the local landscape and plant diversity. Furthermore, the irrigation project will provide sufficient water once established, which will enrich local plant diversity; therefore, we support its construction.